2022
DOI: 10.1097/prs.0000000000008770
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Incision Placement on Ischemic Complications in Microsurgical Breast Reconstruction

Abstract: Background: Nipple-sparing mastectomy is associated with greater patient satisfaction than non–nipple-sparing approaches. Although various nipple-sparing mastectomy incisions have been described, the authors hypothesized that incision location would impact the rate and location of ischemic complications to the mastectomy skin flap. Methods: A prospectively maintained database was queried to identify patients who underwent nipple-sparing mastectomy with immediate microsurgical reconstruction with a minimum po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…The limitations of this study are due to the relatively small sample size, which may have caused the inability to determine the impact of other factors such as BMI and RT on clinical outcomes. Possibly, the IMP‐NSM technique may change the previously described impact of these factors [11, 12, 14, 24, 25]. Future studies of NSM necrosis complications should describe management of the IMP as an important variable that can be modified to decrease necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…The limitations of this study are due to the relatively small sample size, which may have caused the inability to determine the impact of other factors such as BMI and RT on clinical outcomes. Possibly, the IMP‐NSM technique may change the previously described impact of these factors [11, 12, 14, 24, 25]. Future studies of NSM necrosis complications should describe management of the IMP as an important variable that can be modified to decrease necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…We read with great interest the article by Tevlin et al that examined the effects of incision location on ischemic complications of the mastectomy skin envelope after NSM and microvascular breast reconstruction. 1 In a total of 146 reconstructions in 87 patients, the authors reported a significantly greater rate of mastectomy skin flap necrosis with IMF incisions, and a significant association of NAC necrosis with periareolar incisions. The authors should be commended on a meticulously designed study that importantly uses propensity score matching to further reinforce the data on these incision patterns as independent risk factors.…”
mentioning
confidence: 96%